apakah kemampuan guru dalam mengembangkan lembar kerja peserta didik (lkpd) dan instrumen penilaian berbasis media aplikasi kahoot bagi guru sekolah dasar Ngawi dapat meningkat melalui metode pelatihan dan pendampingan? - Riyadi, Riyadi (Didaktika Dwija Indria, 2021)
The fact so far shows the ability of teachers to manage online learning is still low. The purpose of the study was to determine the effect of training and mentoring in the development of student worksheets and kahoot-based assessment instruments for elementary school teachers. This research is a quantitative descriptive study with a one-group pretest-posttest research design. The sample in this study were teachers in Jogorogo District, Ngawi Regency, East Java Province. The data collection technique used is a test. Data were analyzed using N-Gain.The results showed an increase in teacher knowledge of the Kahoot application to develop innovative LKPD. The Pre-test showed an average score of 63.95 while there was an increase in the Post-test with an average score of 70.35. Thus, teachers can improve their pedagogical skills in developing worksheets based on the KAHOOT application.